Do Gender, Financial Income, And Religiosity Influence Indonesian's Donations? - Aris Puji Purwatiningsih; Risky Yuniar Rahmadieni; Harini Abrilia Setyawati; Bakri Abdul Karim (International Journal Ihya' 'Ulum al-Din, 2023)
This study aimed to identify whether gender, financial income, and religiosity influenced Indonesians' donation behavior during the 2021 Covid-19 pandemic. Besides that, its purpose is also to determine which religiosity dimension significantly correlates to the Indonesians' donation intention during the Covid-19 outbreak. The research questions whether gender, financial income, and religiosity influence Indonesian people's donation behavior in the 2021 Covid-19 pandemic era. The data was collected through questionnaires to 334 respondents in 34 provinces in Indonesia that were then analyzed using Partial Least Square (P.L.S.); it was found that financial income, gender, and religiosity significantly influence donation behavior. The religiosity dimension significantly influences donation behavior is the sincerity of Zakat (Islamic charity tax for wealth) paying routine behavior. In contrast, the religion literature study behavior significantly negatively influences the respondents' donation behavior. This study successfully proves that there are influences of gender, financial income, and religiosity on the respondents' donation behavior. This is very important for many stakeholders, like the government, N.G.O.s, and Zakah Institution, so they can formulate policies and strategies to increase the participation of Indonesian in donating.